Factors Influencing the Acceptance of Pediatric Telemedicine Services in China: A Cross-Sectional Study - Shi, Jingjin; Yan, Xueming; Wang, Miao; Lei, Ping; Yu, Guangjun (Frontiers in Pediatrics, 2021)
Background: Pediatrician workforce shortages have aroused great attention from health authorities in China. Telemedicine services have been known to enhance the management of children’s health, yet the rate of adoption and usage in Chinese hospitals still at a quite low level, and the factors influencing the acceptance of telemedicine services remains unclear. Objective: The purpose of this empirical study was to evaluate the reliability and validity of a technology acceptance measurement instrument applied in healthcare, to investigate the perception of telemedicine services on the provider-side and demand-side, and to determine the factors that may drive individuals to adopt telemedicine services. Methods: A cross-sectional survey study based at Shanghai Children’s Hospital, Shanghai Jiao Tong University, was conducted in March 2020. A total of 456 valid responses were obtained by convenience sampling. The internal consistency of items was assessed by Cronbach’s alpha (α), composite reliability (CR) and average variance extracted (AVE) to evaluate both the reliability and validity of the questionnaire. Structural equation modelling analysis was used to test and verify the interrelationships among relevant variables. Results: Price value is the strongest predictor (β=0.30, p=0.02), facilitating conditions (β=0.28, p=0.01) and hedonic motivation (β=0.13, p=0.04) also have significantly positive direct effects on telemedicine acceptance. The results showed the perception of child patients' families were significantly more acceptable to telemedicine services than pediatricians (t=-2.99, p<0.01). Participants with no prior experience and lower education may be more willing to adopt telemedicine. Conclusions: Telemedicine will likely continue to have an integral role in pediatric health care delivery, and the findings can assist policy makers and hospital administrators in determining the more valued characteristics of telemedicine services from a behavioural perspective. Future attention will be paid to the pricing, training and service quality of telemedicine in China.